2020
DOI: 10.3390/en13092353
|View full text |Cite
|
Sign up to set email alerts
|

Underground Pumped-Storage Hydropower (UPSH) at the Martelange Mine (Belgium): Interactions with Groundwater Flow

Abstract: Underground pumped-storage hydropower (UPSH) is a promising technology to manage the electricity production in flat regions. UPSH plants consist of an underground and surface reservoirs. The energy is stored by pumping water from the underground to the surface reservoir and is produced by discharging water from the surface to the underground reservoir. The underground reservoir can be drilled, but a more efficient alternative, considered here, consists in using an abandoned mine. Given that mines are rarely wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Certain authors considered that, initially, the underground reservoir must be empty [50] because previous works needed to adapt the mine to be used as an underground reservoir, and this adaptation requires dewatering it. However, it was proven in a previous investigation that the differences between considering a previous pumping or not are negligible and only occur during the early periods [33].…”
Section: Characteristics Of the Modelmentioning
confidence: 95%
See 1 more Smart Citation
“…Certain authors considered that, initially, the underground reservoir must be empty [50] because previous works needed to adapt the mine to be used as an underground reservoir, and this adaptation requires dewatering it. However, it was proven in a previous investigation that the differences between considering a previous pumping or not are negligible and only occur during the early periods [33].…”
Section: Characteristics Of the Modelmentioning
confidence: 95%
“…Recently, researchers observed that water exchanges may progressively fill the underground reservoir, reducing η. Occasionally, a volume of pumped water could actually not be fully discharged into the underground reservoir because the latter has been partially filled by underground water exchanges [33]. In addition, this volume of water must then be discharged into surface water systems, which could alter their quality because mine water is often not of an appropriate quality.…”
Section: Introductionmentioning
confidence: 99%
“…No operations were scheduled in the 14 hours that were left in a 24-hour period. Such discharge patterns were also generated for the summer and spring periods of 2013 [29]; however, only the discharge curve from the winter period was presented in this study. More detailed explanation on the generation of the discharge patterns is provided by Pujades et al [29].…”
Section: Operation Scenariomentioning
confidence: 99%
“…Such discharge patterns were also generated for the summer and spring periods of 2013 [29]; however, only the discharge curve from the winter period was presented in this study. More detailed explanation on the generation of the discharge patterns is provided by Pujades et al [29]. Due to the fact that in the present study the discharge cycle needed to start with turbining, the first six hours of the original winter discharge time-series, corresponding to a pumping phase [29], were moved to the end of the time-series.…”
Section: Operation Scenariomentioning
confidence: 99%
See 1 more Smart Citation